Management of metastatic thyroid cancer in pregnancy: risk and uncertainty - Christopher W Rowe; Kirsten Murray; Andrew Woods; Sandeep Gupta; Roger Smith; Katie Wynne (Endocrinology, Diabetes & Metabolism Case Reports, 2016)
Metastatic thyroid cancer is an uncommon condition to be present at the time of pregnancy, but presents a challenging paradigm of care. Clinicians must balance the competing interests of long-term maternal health, best achieved by iatrogenic hyperthyroidism, regular radioiodine therapy and avoidance of dietary iodine, against the priority to care for the developing foetus, with inevitable compromise. Additionally, epidemiological and cellular data support the role of oestrogen as a growth factor for benign and malignant thyrocytes, although communicating the magnitude of this risk to patients and caregivers, as well as the uncertain impact of any pregnancy on long-term prognosis, remains challenging. Evidence to support treatment decisions in this uncommon situation is presented in the context of a case of a pregnant teenager with known metastatic papillary thyroid cancer and recent radioiodine therapy.